Modelagem dinâmica para simulação no processo de arenização e cobertura florestal na campanha ocidental - RS - Silva, Emanuel Araújo (2015)
The dynamic modeling process is a useful tool for the knowledge of land use and occupation, creating methodological guidelines associated to ambient, social and economical issues. This work aims to establish a model to simulate the dynamic in the sandfication process and forest cover at South-west of Rio Grande do Sul, named micro regions of Campanha Ocidental and, based on this technics, make a future scenery projection. An image mosaic of LANDSAT 5 satellite was used, which recovers the studied region in the years of 1985, 1996, 2011 and LANDSAT 8 in 2013 year. SPRING was used to data base elaboration and data processing of digital images. After the image classification, the LEGAL program was used to develop the cross thematic maps, which will be used on simulations for the future sceneries by modeling with Dinamica EGO software. The expected results for 2026 indicate that forest cover will increase from 14.22% in 2011 to 15,03% in the year 2026 the total area of the Campanha Ocidental, showing that the expansion of forest cover is in the process of stabilization, focusing the areas in east, high altitudes and around drainage rivers. In the sand, this projection will retracts from 0.37% in 2011 to 0.33% in 2026, its concentration will be in the northeast, high altitudes and around the Ibicuí river drainage.